Pelatihan Penelitian Tindakan Kelas Bagi Guru-Guru SD Dan SMP Di Kecematan XIII Koto Kampar - Mimi Mimi Yulianti; Rika Ningsih; Alnisa Riskya Putri Maharani (Jurnal Berkarya Pengabdian Masyarakat, 2022)
The purpose of this community service activity is to provide training on the procedures for writing classroom action research to elementary and junior high school teachers in District XIII Koto Kampar. The material provided in this training relates to the procedures for writing CAR, the methods used in writing CAR and the output of CAR writing. From this activity, it is hoped that there will be many scientific works in the form of CAR that can be produced by elementary and junior high school teachers in the District XIII Koto Kampar. This activity was attended by 20 teachers.